Hukum Laut di Indonesia - Ardifka, Fran; Rahman, Fathur; Pakpahan, Rori Chandra Zaqy; Idrus, Muhammad; Alam, Samsir (Pusdikra Publishing, 2024)
Indonesian, as an archipelagic country with a large maritime area, has significant maritime legal interests in its national legal system. Despite its importance, Indonesia's maritime law is still fragmented and lacks a comprehensive and coherent framework. The study aims to analyze and review existing maritime laws and regulations in Indonesia, identify gaps and inconsistencies, and propose a new framework for Indonesian maritime law. This study uses a qualitative research approach, analyzing primary and secondary legal sources, as well as conducting interviews with experts in the field. The results of the study show that Indonesia's maritime law is filled with inconsistencies and lack of clarity, leading to confusion and uncertainty among stakeholders. The study proposes a new framework that integrates existing laws and regulations, provides clear definitions and procedures, and ensures the effective management of Indonesia's vast maritime territory